2016
DOI: 10.1371/journal.pone.0161203
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Abscisic Acid in PSII Photodamage and D1 Protein Turnover for Light-Induced Premature Senescence of Rice Flag Leaves

Abstract: D1 protein in the PSII reaction center is the major target of photodamage, and it exhibits the highest turnover rate among all the thylakoid proteins. In this paper, rice psf (premature senescence of flag leaves) mutant and its wild type were used to investigate the genotype-dependent alteration in PSII photo-damage and D1 protein turnover during leaf senescence and its relation to ABA accumulation in senescent leaves. The symptom and extent of leaf senescence of the psf mutant appeared to be sunlight-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 57 publications
(136 reference statements)
0
38
0
Order By: Relevance
“…Shading induces premature plant leaf senescence, especially under weak natural light conditions [ 39 ]. Complete shading (i.e., darkness) is an important factor contributing to leaf senescence [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shading induces premature plant leaf senescence, especially under weak natural light conditions [ 39 ]. Complete shading (i.e., darkness) is an important factor contributing to leaf senescence [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress promoted premature leaf senescence by phytohormone regulatory factors, particularly ABA homeostasis mechanisms (Asad et al, 2019). ABA acts as an important regulator in age-dependent physiological processes from seed germination to leaf senescence (Nambara and Marion-Poll, 2005;Wang et al, 2016;Liao et al, 2018). ABA homeostasis mechanism in ABA-mediated leaf senescence initiates from ABA biosynthesis and catabolism, ABA transport, and ABA signaling receptors (Asad et al, 2019).…”
Section: Physiological Action Of Hda9 In Aba-dependent Drought Stressmentioning
confidence: 99%
“…Qian et al (2009) showed that copper and cadmium inhibited the expression of psbA at the transcriptional level in Chlorella vulgaris. Wang et al (2016) reported that the transcriptional expression of several key genes ( psbA, psbB, psbC and OsFtsH2) involved in D1 protein biosynthesis and PS II repair cycle was seriously suppressed in senescent leaves.…”
mentioning
confidence: 99%